Darbepoietin alpha: pharmacokinetics and clinical use in neonates (Hematology Meeting Reports, 2009)
Many hyporegenerative anemias in adults result from insufficient erythropoietin production, and the administration of recombinant human erythropoietin effectively stimulates red cell production. A biologically modified erythropoietic protein with a significantly longer half-life, darbepoetin alfa (Aranesp®), was developed by Amgen to allow for less frequent dosing. Studies in adults showed that darbepoetin alfa increased hemoglobin using once weekly to once every three week dosing. Studies evaluating the effectiveness of darbepoetin in treating other hyporegenerative anemias in adults and children are ongoing. Single dose pharmacokinetics have been determined in preterm infants, and phase II neonatal studies are in progress.